2019
DOI: 10.3329/bjp.v14i2.39254
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemic potential of Trixis angustifolia aqueous extract in alloxan-induced diabetic mice

Abstract: The aim of the present study was to evaluate the hypoglycemic potential of Trixis angustifolia in alloxan-induced diabetic mice. An intragastric administration of the aqueous extract (50, 100 and 200 mg/kg) prepared from the aerial parts of T. angustifolia was evaluated. The treatment with the extract at 100 mg/kg produced a significant lowered (30.5%) of the blood glucose levels in diabetic mice after 15 days of daily oral administration. In addition, the extract induced a significant decrease in serum total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The anti-diabetic activities of Achillea santolina (Grover et al, 2002), Adiantum capillus-veneris (Al-Snafi, 2013), Agrimony eupatoria (Al-Snafi, 2015), Aristolochia longa (El Omari et al, 2019), Atractylis gummifera (Bouabid et al, 2019), Eruca sativa (Kishore et al, 2017), Gaultheria trichophylla (Alam and Saqib, 2017), Leucas aspera (Annapandian and Sundaram, 2017), Myrica gale, Rhodiola rosea, Rumex acetosa, Taraxacum officinale (Sekhon-Loodu and Rupasinghe, 2019), Trixis angustifolia (Salazar-Gómez et al, 2019) and Urtica dioica (Ahangarpour et al, 2012) have been reported. um phosphate dibasic, DPPH (2, 2-diphenyl-1-picrylhydrazyl), ABTS•+ (2,2-azinobis (3-ethyl-benzothiazoline)-6-sulfonic acid disodium salt), hydrogen peroxide, amylase, DNS (dinitrosalicylic) acid, sea salts, glucophage, potassium persulfate were of analytical grade.…”
Section: Introductionmentioning
confidence: 99%
“…The anti-diabetic activities of Achillea santolina (Grover et al, 2002), Adiantum capillus-veneris (Al-Snafi, 2013), Agrimony eupatoria (Al-Snafi, 2015), Aristolochia longa (El Omari et al, 2019), Atractylis gummifera (Bouabid et al, 2019), Eruca sativa (Kishore et al, 2017), Gaultheria trichophylla (Alam and Saqib, 2017), Leucas aspera (Annapandian and Sundaram, 2017), Myrica gale, Rhodiola rosea, Rumex acetosa, Taraxacum officinale (Sekhon-Loodu and Rupasinghe, 2019), Trixis angustifolia (Salazar-Gómez et al, 2019) and Urtica dioica (Ahangarpour et al, 2012) have been reported. um phosphate dibasic, DPPH (2, 2-diphenyl-1-picrylhydrazyl), ABTS•+ (2,2-azinobis (3-ethyl-benzothiazoline)-6-sulfonic acid disodium salt), hydrogen peroxide, amylase, DNS (dinitrosalicylic) acid, sea salts, glucophage, potassium persulfate were of analytical grade.…”
Section: Introductionmentioning
confidence: 99%
“…5 In traditional Mexican medicine, the aerial parts of T. angustifolia have been used as a water-extract formulation to reduce blood glucose in alloxan-induced diabetic mice. 6 However, there is no literature about the hypolipidemic activity of this species that supports the ethnomedical usage of the plant. Therefore, the present study was conducted to evaluate the hypolipidemic effect of T. angustifolia aqueous extract (TxAE) on Triton WR-1339- and high-fat diet-induced hyperlipidemic mice.…”
mentioning
confidence: 98%
“…As far as we know, there is only 1 phytochemical screening regarding the use of water as solvent for the extraction of T. angustifolia constituents. 6 This is important since popular use occurs more frequently with infusions, decoctions, and macerations, and little is known about the constitution of this kind of extract. Thus, as part of the phytochemical study, we have determined the phenolic composition of TxAE.…”
mentioning
confidence: 99%